Gravitational wave background from vacuum and thermal fluctuations during axion-like inflation. Issue 12 (1st December 2022) - Klose, P.; Laine, M.; Procacci, S.
Abstract: We revisit the framework of axion-like inflation in view of the possibility that the coupling of the inflaton to a non-Abelian topological charge density could lead to the generation of a rapidly thermalizing heat bath. Both dispersive (mass) and absorptive (friction) effects are included. For phenomenologically viable parameters, the system remains in a weak regime of warm inflation (thermal friction ≪ Hubble rate). For tensor perturbations we derive an interpolating formula that incorporates both vacuum and thermal production. The latter yields a model-independent frequency shape ∼ f 0 3 in the LISA window, whose coefficient allows to measure the maximal shear viscosity of the thermal epoch. It is a challenge, however, to find models where the coefficient is large enough to be observable.